Outcomes and Predictors of Outcome with Cisternostomy in the Management of Traumatic Brain Injury—A Prospective Observational Study at a Tertiary Centre - Vemula, Ramesh Chandra; Prasad, BCM; Banavath, Hanuma Naik; Kale, Pavan Kumar G; Krishna N, Mohana Murali; Gokanapudi, Sreeram (Indian Journal of Neurotrauma, 2022)
Background Traumatic brain injury (TBI) is a major cause of morbidity and mortality in young individuals. Goal of management in TBI patients is mainly focused on the secondary injury. Since the cisterns and the brain communicate, it would be possible to decrease the pressure in both these compartments by opening the cisterns to the atmospheric pressure.Objective To study the outcomes and predictors of outcome with cisternostomy in the management of TBI.Methods A single tertiary care center's prospective observational study of outcomes with cisternostomy with intraoperative intracranial pressure (ICP) monitoring. Patients were evaluated clinically and radiologically with Marshall CT score. They were categorized into mild, moderate, and severe head injury groups based on Glasgow coma scale (GCS) score. Outcomes were evaluated with Glasgow outcome scale (GOS) score.Results A total of 25 patients with TBI were enrolled in this study. They underwent cisternostomy with intraoperative ICP monitoring. They were categorized into 4 groups based on the age. In our study, mortality rate was 32%. As much as 48% had good recovery at 3 months follow-up with GOS 4 and 5. Mean ICP after cisternostomy was 6.36 ± 1.91 mm Hg. In our study, there was decrease in ICP after cisternostomy.Conclusion Age, time interval from trauma to surgery, and ICP showed prognostic importance on outcomes. Cisternostomy can efficiently decrease the ICP in the TBI patients and reduce postoperative complications.
Keywords: Cisternostomy; head injury; recent advances in neurotrauma; surgery for neurotrauma; traumatic brain injury